Pengaruh Variasi Senam terhadap Tingkat Kebugaran Jasmani Siswa Kelas V SDN 091486 Afd IV/V Bahbirongulu Kecamatan Jorlang Hataran - Rahel Insaniar Manik; Khairul Usman (Institut Nalanda, 2024)
This study aims to determine the effect of gymnastic variations on the level of physical fitness of class V SD Negeri 091486 Afd IV/V Jorlang Hataran T.A 2023/2024. This research is an experimental research with an experimental approach. The sample used in this study were grade V students totaling 24 students. The research instrument consisted of (1) Interview sheet related to the results of the variation of rhythmic gymnastics in the school, and (2) Test instrument using Sports Faal to determine the results of students' physical fitness. The data analysis technique was carried out descriptively and continued with a non-parametric test using the Waxicon Test to determine whether there was a difference in the average of the two samples.Based on descriptive statistical data analysis, the average pre test result is 2.3 and the post test is 3.4. Then in the non-parametric test it is known that Asymp.Sig (2-tiled) is 0.000 because the value of 0.000 <0.50, it can be concluded that